Do People's Desires to Change Their Personality Traits Vary With Age? An Examination of Trait Change Goals Across Adulthood. (November 2016) - Hudson, Nathan W.; Fraley, R. Chris
Research suggests most people want to change their personality traits. Existing studies have, however, almost exclusively examined college-aged samples. Thus, it remains unclear whether older adults also wish to change their personalities. In the present study, the authors sampled 6, 800 adults, aged 18 to 70, and examined the associations between age and change goals. Results indicated change goals were slightly less prevalent among older adults. Moreover, older adults expressed desires for slightly smaller increases in each trait. Nevertheless, these effects were small, and a minimum of 78% of people of any age wanted to increase in each big five dimension. These findings have implications for understanding people's attempts to change their traits—and personality development more broadly—across adulthood.